The relationships between perfectionism, epistemic beliefs, self-efficacy, and achievement goals in mathematics - Rovan, Daria (Array, 2012)
This paper explores perfectionism, epistemic beliefs and self-efficacy as proposed antecedents of students' achievement goals in the context of learning mathematics in higher education. A sample of 362 undergraduate technical sciences students enrolled in introductory-level mathematics course participated in the study. Students completed questionnaire on perfectionism (adaptive and maladaptive), epistemic beliefs (simplicity and justification of knowledge in mathematics), self-efficacy and achievement goals in mathematics. Results revealed that mastery- approach and performance-approach goals were positively predicted by adaptive perfectionism and justification of knowledge, but negatively predicted by simple knowledge. Self- efficacy beliefs also positively predicted performance-approach goals. Mastery-avoidance and performance-avoidance goals were positively predicted by both maladaptive and adaptive perfectionism. This research advances our understanding of how individual differences in students' beliefs and standards that they set may influence their achievement goal pursuit.